2012
DOI: 10.5296/jee.v3i1.2674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physico-chemical Parameters on Phytoplankton of a Tidal Creek, Lagos, Nigeria

Abstract: Physico-chemical parameters have been observed to influence phytoplankton composition of coastal areas and water in Nigeria. In order to assess this, the phytoplankton composition of a tidal creek in Lagos was investigated in relation to the physico-chemical characteristics for twelve months (February 2010-January 2011. Six stations were created, phytoplankton samples were collected using 55µm mesh size plankton net and water samples were also collected for physico-chemical parameters analysis. Four major divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The presence and dominance of diatoms in the sampling areas conformed with observation made by Nwadiaro (1990) in the chanomi creek system of the Niger Delta, Chindah and Pudo (1991) in Bonny River, Erondu and Chindah (1991) in the new Calabar River, Niger Delta, Nwankwo (2005, 2008) in Olero and Abule-Eledu creek respectively, in Ogbe creek and Adesalu and Kunrunmi (2012) in the Lagoons of South-Western Nigeria.…”
Section: Discussionsupporting
confidence: 85%
“…The presence and dominance of diatoms in the sampling areas conformed with observation made by Nwadiaro (1990) in the chanomi creek system of the Niger Delta, Chindah and Pudo (1991) in Bonny River, Erondu and Chindah (1991) in the new Calabar River, Niger Delta, Nwankwo (2005, 2008) in Olero and Abule-Eledu creek respectively, in Ogbe creek and Adesalu and Kunrunmi (2012) in the Lagoons of South-Western Nigeria.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Abdul et al (2015) also reported 6 phytoplankton divisions in Ogun state coastal estuary which is a portion of the study area but higher number of species (42) was recordedcompared to the present study. Dushyant and Singh (2013) and Adesalu (2012) recorded higher number of species (117 and 61 respectively) in Tighra Reservoir, India and Majidun creek of Lagos lagoon, Nigeria. However, the number of divisionsrecorded by both authors (4 and 3divisions respectively) was lower than the number recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then preserved in 4% formalin as described by Ogbuagu and Ayoade (2012) and Sharma et al (2015). Samples were obtained during daylight between 11am and 2pm so as to minimize variations as a result of the diurnal migration of plankton (Adesalu, 2012).…”
Section: Sampling Of Phytoplankton and Environmental Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, algological studies on lotic system are gaining interest but necessarily that of national parks and include that of Kadiri and Azomani (2000) who studied the effect of brewery effluent on the growth of two chlorophytes in Ikpoba River, Kadiri and Omozusi (2002) reported the phytoplankton of River Okhuahe in Benin, Kadiri (2007) reported the phytoplankton of River Ethiope. Most recent phycological information in similar freshwater bodies are available in Akoma and Opute (2010), Nwankwo (2010, 2012), Alika and Akoma (2012), Adesalu et al https://dx.doi.org/10.4314/ijs.v19i2.7 (2010Adesalu et al https://dx.doi.org/10.4314/ijs.v19i2.7 ( , 2016aAdesalu et al https://dx.doi.org/10.4314/ijs.v19i2.7 ( , 2016b, Ekhator et al (2014Ekhator et al ( , 2015, Adesalu (2016), Adesalu and Kunrunmi (2016), Akinyemi and Adesalu (2016). Of all mentioned work above, Okomu National Park water bodies and several other national parks except River Oli in Kainji Lake National park (Adesalu, 2010) water bodies remain without phycological information hence such studies remain important because majority of the riverine inhabitant most of the time, depend on their surrounding water (River) apart from rain water for their water needs.…”
Section: Introductionmentioning
confidence: 99%